Memoirs red and white : Poland, the war, and after - Dembowski, Peter F. (Peter Florian), 1925- (University of Notre Dame Press, 2015)
"'Like the Polish flag, composed of two contrasting colors, red and white, my memoirs are cast in red and white. 'Red' treats largely my wartime life in Europe, life full of blood and death. My success in that part of my life was survival. 'White' represents my successful migration and peaceful life in America'--from the Preface; Born after World War I into an educated and progressive Polish family, Peter F. Dembowski was a teenager during the joint occupation of Poland by Nazi Germany and the Soviet Union. His account of life as a young Polish soldier, as an immigrant to Canada, and finally as an American professor is a gripping narrative of life before, during, and after the horrors of World War II. Skillfully weaving a tapestry of emotion and history, Dembowski recounts the effects of loss: at age twelve, his father's death; and later, the arrest of his mother and sister by the Gestapo and their execution in 1942 in the women's concentration camp of Ravensbruck. Balancing those tragedies, Dembowski recalls the loving care given him by Janina Dembowska, the wife of his paternal uncle, as well as the inspiring strength of character he witnessed in his teachers and extended family. Still a very young-looking teenager, Dembowski became involved with the Polish Underground in 1942. Suspected as a konspirator, he was incarcerated in Pawiak Prison and later, after a rare release, fought in the Warsaw Uprising of 1944. His on-the-ground account describes the deprivations Polish soldiers faced as well as the fierce patriotism they shared. With the defeat of the Uprising, he was deported to Sandbostel; once liberated, he joined the Polish Army in Italy, serving there for two years. In 1947, Dembowski made the momentous decision not to return to Poland but rather to emigrate to Canada. We learn of his stint as a farmhand and, later, of his studies at the University of British Columbia in Vancouver. He continued his education in France, receiving a Doctorat from l'Universite de Paris in Russian philology and, in 1960, a PhD from the University of California at Berkeley in medieval French. In tandem with his successful academic career teaching at the University of Toronto and at the University of Chicago, Dembowski describes his happy marriage and the joy of family life; 'Peter F. Dembowski's Memoirs Red and White : Poland, the War, and After is the moving testimony of an individual who has had firsthand knowledge of the most dramatic moments in the history of the twentierth century. His story is one of heroic courage, honesty, and optimism'--Thomas Pavel, Gordon J. Laing Distinguished Service Professor in Romance Languages and Literature, University of Chicago"--